PANCASILA AS THE PHILOSOPHICAL FOUNDATION OF THE INDONESIAN CURRICULUM - Pulhehe, Nurbaya; Robandi, Babang (Paradigma: Jurnal Kajian Budaya, 2024)
The philosophical foundation of Pancasila, comprised of five principles, plays a significant role in shaping Indonesia's education system. These principles guide curriculum design, implementation, and evaluation, reflecting the nation's educational goals and desired student outcomes. This paper examines the philosophical underpinnings of Pancasila, with a focus on content and graduate competence standards, examining their relationship with educational objectives and their implications for the national curriculum. Utilizing a literature review methodology, the research highlights the critical influence of Pancasila on curriculum development and educational planning in Indonesia. The findings indicate that Pancasila serves as a central philosophical framework guiding Indonesia's national education system, with a particular emphasis on character education, tolerance, citizenship education, and inclusive learning. The study reviews the evolution of content and graduate competence standards in Indonesian education, drawing attention to changes in government regulations and the philosophical assumptions of Pancasila. However, further research is recommended to explore the influence of these assumptions on other educational standards.